Thrift Traders' Survival Strategy After the Issuance of the Used Clothes Import Policy at the Comboran Market, Indonesia - Pratama, Ilyas Shaso; Adi, Khofifatu Rohmah; Ratnawati, Nurul (Humanities Horizon, 2024)
This research was conducted at the Comboran Market on Prof. Moch Yamin Street, Sukoharjo, Klojen District, Malang City with the following objectives: 1) to describe the background of thrift traders selling at the Comboran Market, and 2) to describe the survival strategy of thrift traders after the issuance of the policy of importing used clothes in the Comboran Market. This study uses a descriptive qualitative method. Data analysis uses the interactive model of Miles, Huberman, and Saldana. The results of this study reveal that the background of Thrift traders in the Comboran Market is due to the potential for great interest in used clothing buyers in the Comboran Market and generate income with large profits. The name of the second-hand goods market has become an identity for the Comboran Market, and its location is easily accessible because it is in the middle of the city. The survival strategy of thrift traders after the issuance of the policy of banning the import of used clothes is with an active strategy, namely by maintaining existing potential such as utilizing family members as workers and being selective in choosing merchandise. The passive strategy is not to buy bales of used clothes at the agency, however, look for branded used clothes and buy them at a low price and resell them at a price that can make a profit. Also, a network strategy by building good relationships with agents and buyers so that daily needs can be met.